Новый вид рода Saruga и положение этого рода среди Pachygasterinae (Diptera, Stratiomyidae) - Кривошеина, Н.П. (Вестник зоологии, 1993)
Saruga esenini sp. n. is described from Viet-Nam; reality of the genus is confirmed by conic scutellum, sharply differing it from representatives of other genera with elongated thin scutellum. Type material of (lie new species is deposited at the Institute of Evolutionary Morphology and Ecology, the Russian Academy of Sciences (Moscow).